'Art-horror' and 'hardcore art-horror' at the margins: Experimentation and extremity in contemporary independent horror. Issue 1 (1st March 2021) - Falvey, Eddie
The changing forms of contemporary horror have been the subject of much discussion, both in popular journalism and scholarship. Amid an on-going discussion on the arrival and characteristics of what has been contentiously termed 'post-horror', this article seeks to situate recent independent American horror within the context of the recent art film, in keeping with the work of Geoff King, as well as the traditions of 'art-horror' as it has been referred to by Joan Hawkins. Using a series of examples taken from recent independent horror ‐ including A Ghost Story (David Lowery 2017) and The Lighthouse (Robert Eggers 2019), as well as the micro-budget independent films of Phil Stevens ‐ Falvey makes use of King's work to explore the textual characteristics of recent 'art-horror'. Falvey argues that films iterative of this mode employ experimentation and extremity (in various forms) to discursively position the films away from more generically recognizable studio horror films in a bid for critical distinction.